Dependence of Raman Spectral Intensity on Crystal Size in Organic Nano Energetics. Issue 8 (August 2016) - Patel, Rajen B.; Stepanov, Victor; Qiu, Hongwei
Raman spectra for various nitramine energetic compounds were investigated as a function of crystal size at the nanoscale regime. In the case of 2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane (CL-20), there was a linear relationship between intensity of Raman spectra and crystal size. Notably, the Raman modes between 120 cm −1 and 220 cm −1 were especially affected, and at the smallest crystal size, were completely eliminated. The Raman spectral intensity of octahydro-1, 3, 5, 7-tetranitro-1, 3, 5, 7-tetrazocine (HMX), like that of CL-20's, depended linearly on crystal size. The Raman spectral intensity of 1, 3, 5-trinitroperhydro-1, 3, 5-triazine (RDX), however, was not observably changed by crystal size. A non-nitramine explosive compound, 2, 4, 6-triamino-1, 3, 5- trinitrobenzene (TATB), was also investigated. Its spectral intensity was also found to correlate linearly with crystal size, although substantially less so than that of HMX and CL-20. To explain the observed trends, it is hypothesized that disordered molecular arrangement, originating from the crystal surface, may be responsible. In particular, it appears that the thickness of the disordered surface layer is dependent on molecular characteristics, including size and conformational flexibility. Furthermore, as the mean crystal size decreases, the volume fraction of disordered molecules within a specimen increases, consequently, weakening the Raman intensity. These results could have practical benefit for allowing the facile monitoring of crystal size during manufacturing. Finally, these findings could lead to deep insights into the general structure of the surface of crystals.